Synthesis and conformation of a novel fluorescein–Zn-porphyrin dyad and intramolecular energy transfer. (7th March 2016) - Rezazgui, Olivier; Trouillas, Patrick; Qiu, Shi-hong; Siegler, Benjamin; Gierschner, Johannes; Leroy-Lhez, Stephanie
Abstract : Modulations of the optical properties of a new porphyrin–fluorescein dyad were elucidated using experimental and theoretical techniques, with conformational rearrangements being studied. Abstract : This study describes the synthesis and characterization of a new zinc porphyrin–fluorescein dyad, the two chromophoric units being covalently linked by a 1, 2, 3-triazole bridge. The latter was formed by Cu-catalyzed Huisgen 1, 3-dipolar cycloaddition. The conformational analysis of this dyad (1 ) was performed by NOESY experiments, suggesting interactions between moieties; density functional theory (DFT) calculations confirmed clear evidence of a folded conformer, which is stabilized by electrostatic and CH–π interactions. Photophysical measurements demonstrated solvent-dependent energy transfer, with an efficiency of about 40%.